Kerusakan Ekologis Hutan Jati Di Kabupaten Muna (Potret Pemujaan Pendekatan Anthroposentris) - Muhammad Ali Azhar (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2007)
Regional autonomy has been said as the key factor affecting forest degradation in Muna Regency. Local government policy in allowing both local community and bussines actors to exploit 'Jati' forest in the name of local government income mirrors the domination of the logic of rational-anthropocentrism over local wisdom in managing natural resources. This paper suggests to bring back traditional values, root in the Local society, in managing the forest. Such way is believed to balance the need of economic resources and natural preservation.